Schaum's outline trigonometry : with calculator-based solutions - Moyer, Robert E.; Frank Ayres, Jr. (New York : McGraw Hill Education, 2013)
From the Publisher: Schaum's has Satisfied Students for 50 Years. Now Schaum's Biggest Sellers are in New Editions! For half a century, more than 40 million students have trusted Schaum's to help them study faster, learn better, and get top grades. Now Schaum's celebrates its 50th birthday with a brand-new look, a new format with hundreds of practice problems, and completely updated information to conform to the latest developments in every field of study. Schaum's Outlines-Problem Solved. More than 500,000 sold! This thorough review of standard college courses in trigonometry has been updated to reflect the latest course scope and sequences. The new edition includes expanded explanations of the aspects of each periodic function, and updated information for the curve graphing section.
1: Angles And Applications -- 1-1: Introduction -- 1-2: Plane angle -- 1-3: Measures of angels -- 1-4: Arc length -- 1-5: Lengths of arcs on a unit circle -- 1-6: Area of a sector -- 1-7: Linear and angular velocity -- 2: Trigonometric Functions Of A General Angle -- 2-1: Coordinates on a line -- 2-2: Coordinates in a plane -- 2-3: Angles in standard position -- 2-4: Trigonometric functions of a general angle -- 2-5: Quadrant signs of the functions -- 2-6: Trigonometric functions of quadrantal angles -- 2-7: Undefined trigonometric functions -- 2-8: Coordinates of points on a unit circle -- 2-9: Circular functions -- 3: Trigonometric Functions Of An Acute Angle -- 3-1: Trigonometric functions of an acute angle -- 3-2: Trigonometric functions of complementary angles -- 3-3: Trigonometric functions of 30 degrees, 45 degrees, and 60 degrees -- 3-4: Trigonometric function values -- 3-5: Accuracy of results using approximations -- 3-6: Selecting the function in problem solving -- 3-7: Angles of depression and elevation -- 4: Solutions Of Right Triangles -- 4-1: Introduction -- 4-2: Four-place tables of trigonometric functions -- 4-3: Tables of values for trigonometric functions -- 4-4: Using tables to find an angle given a function value -- 4-5: Calculator values of trigonometric functions -- 4-6: Find an angle given a function value using a calculator -- 4-7: Accuracy in computed results -- 5: Practical Applications -- 5-1: Bearing -- 5-2: Vectors -- 5-3: Vector addition -- 5-4: Components of a vector -- 5-5: Air navigation -- 5-6: Inclined plane -- 6: Reduction To Functions Of Positive Acute Angles -- 6-1: Coterminal angles -- 6-2: Functions of a negative angle -- 6-3: Reference angles -- 6-4: Angles with a given function value -- 7: Variation And Graphs Of The Trigonometric Functions -- 7-1: Line representations of trigonometric functions -- 7-2: Variations of trigonometric functions -- 7-3: Graphs of trigonometric functions -- 7-4: Horizontal and vertical shifts -- 7-5: Periodic functions -- 7-6: Sine curves. 8: Basic Relationships And Identities -- 8-1: Basic relationships -- 8-2: Simplification of trigonometric expressions -- 8-3: Trigonometric identities -- 9: Trigonometric Functions Of Two Angles -- 9-1: Addition formulas -- 9-2: Subtraction formulas -- 9-3: Double-angle formulas -- 9-4: Half-angle formulas -- 10: Sum, Difference, And Product Formulas -- 10-1: Products of sines and cosines -- 10-2: Sum and difference of sines and cosines -- 11: Oblique Triangles -- 11-1: Oblique triangles -- 11-2: Law of sines -- 11-3: Law of cosines -- 11-4: Solution of oblique triangles -- 12: Area Of A Triangle -- 12-1: Area of a triangle -- 12-2: Area formulas -- 13: Inverses Of Trigonometric Functions -- 13-1: Inverse trigonometric relations -- 13-2: Graphs of the inverse trigonometric relations -- 13-3: Inverse trigonometric functions -- 13-4: Principal-value range -- 13-5: General values of inverse trigonometric relations -- 14: Trigonometric Equations -- 14-1: Trigonometric equations -- 14-2: Solving trigonometric equations -- 15: Complex Numbers -- 15-1: Imaginary numbers -- 15-2: Complex numbers -- 15-3: Algebraic operations -- 15-4: Graphic representation of complex numbers -- 15-5: Graphic representation of addition and subtraction -- 15-6: Polar or trigonometric form of complex numbers -- 15-7: Multiplication and division in polar form -- 15-8: De Moivre's theorem -- 15-9: Roots of complex numbers -- Appendix 1: Geometry -- A1-1: Introduction -- A1-2: Angles -- A1-3: Lines -- A1-4: Triangles -- A1-5: Polygons -- A1-6: Circles -- Appendix 2: Tables -- Table 1: Trigonometric functions: Angle in 10-minute intervals -- Table 2: Trigonometric functions: Angle in tenth of degree intervals -- Table 3: Trigonometric functions: Angle in hundredth of radian intervals -- Index.
Includes index.
Keywords: TRIGONOMETRY -- PROBLEMS, EXERCISES, ETC